THE ROLE OF ARTIFICIAL INTELLIGENCE AND INNOVATIVE TECHNOLOGIES IN ENHANCING FOREIGN LANGUAGE TEACHING - Khudoyarova Ziyoda Maratovna (Bright Mind Publishing, 2025)
In the context of globalization, foreign language teaching is being enriched by innovative approaches and artificial intelligence technologies. This article analyzes the potential of AI-powered educational platforms and interactive applications to personalize the learning process and enhance its effectiveness. The study examines the impact of modern technologies on education based on statistical data and proposes promising directions for future development.
Keywords: Foreign language teaching, innovative approach, artificial intelligence, educational technologies, individualized learning.